Planning, risk, and property development : urban regeneration in the England, France, and the Netherlands - Karadimitrio, Nikos; Magalhês, Claudio de; Verhage, Roelof, 1971- (NY: Routledge, 2013)
Includes bibliographical references (p. [216]-224) and index.